Characteristics Analysis of Combined Cycle Coupled With High Temperature Gas-Cooled Reactor Based on Progressive Optimization - Qu, Xinhe; Yang, Xiaoyong; Wang, Jie (Frontiers in Energy Research, 2022)
Owing to the current serious environmental and climate problems, the energy industry must focus on the problem of energy utilization rates. High-temperature gas-cooled reactors (HTGRs) are fourth-generation reactors, characterized by high outlet temperatures. The combined cycle is composed of the gas turbine and steam turbine cycles, and it can realize the cascade utilization of high-quality energy. It is a highly competitive power conversion scheme for HTGRs. In this study, the matching characteristics of the combined cycle coupled with HTGRs are revealed through the progressive optimization method. In the combined cycle coupled with HTGRs, the topping and bottoming cycle are both closed cycles, therefore, the optimization for cycle efficiency is to match the topping and bottoming cycles. For a combined cycle with subcritical steam parameters, there are two extreme values of the combined cycle efficiency that have different power ratios. The characteristics revealed in this study are unique to closed combined cycle coupled with HTGRs.